Assessment of Mulch Material Effect on Surface Runoff, Soil Loss, and Water Quality in an Agricultural Region - Riyanto Haribowo; Runi Asmaranto; ‪L. Tri Wijaya Nata Kusuma; Berlian Gari Amrina (AGRIVITA, Journal of Agricultural Science, 2022)
This research aims to determine the type of mulch material that effectively reduces the risk of erosion on agricultural lands and gives minimum detrimental impacts on water quality. The S12 Advanced Environmental Hydrology System used for rainfall simulator. Rainfall intensity was set up based on the daily annual maximum rainfall data. Meanwhile, the land slope is according to research site contour. This research was designed to compare the conditions of soil without mulch (WM) and Rice Straw Mulch (RSM), Mendong Biogeotextile Mulch (MBM), and Plastic Mulch (PM). The observed quality parameters were Dissolved Oxygen (DO), pH, and Total Dissolved Solids (TDS). Statistical analysis involved a three-way analysis of variance (ANOVA) with the aid of SPSS 26 software. Based on the smallest mean values for the amount of surface runoff discharge (mean 1.10), amount of sediment yield (mean 0.650), change in pH (mean 7.48), and TDS (mean 0.24) value, it can be concluded that MBM is the most optimal to be utilized as soil cover for agricultural lands. The performance of MBM is better than RSM and PM.